Changes in atmospheric deposition and streamwater chemistry over 25 years in undisturbed catchments in a Mediterranean mountain environment. - Avila, Anna; Rodà, Ferran (The Science of the total environment, 2012)
Surface water chemistry has changed in response to reduced atmospheric deposition of sulphur and acidity in many regions of Europe and North America. Most of these studies come from acidic or low-alkalinity surface waters under high acidic deposition. Mediterranean climates offer a different biogeochemical context, characterised by streamwaters of higher alkalinity and low acid inputs. In this paper, we use surveys of streamwater chemistry conducted in 1981-1984 and again in 2007 in the Montseny natural park (NE Spain) to test whether streamwaters of these well-buffered catchments respond to changes in atmospheric deposition, which has declined for S during the last decades in NE Spain while remaining about stable for nitrogen. The 23 sampled streams drained heathland, beech forests and evergreen oak forests in relatively undisturbed small catchments underlain by silicate bedrock. Bulk deposition of sulphate at Montseny decreased by 54% while nitrate bulk deposition increased (non-significantly) by 30% in this period. Total N deposition is estimated in the range 15-30 kg N ha(-1) y(-1) for NE Spain. This is well above threshold values (e.g. 10 kg N ha(-1) y(-1)) reported as starting nitrogen saturation symptoms in forest ecosystems in Europe. Baseflow sulphate concentrations decreased on average by 47 μeq L(-1) or 29% of early 1980s concentrations. Baseflow mean nitrate concentrations increased significantly but only from 5.5 to 8.9 μeq L(-1). Thus, despite decades of high N deposition, these ecosystems appear to be still far from N saturation. Baseflow alkalinity and base cation concentrations increased substantially, probably a combined result of decreased S deposition, enhanced silicate weathering under current higher temperatures, reduced plant cation uptake as vegetation matures, and slightly drier conditions in the survey of 2007. Overall, these well-buffered catchments have shown sizable changes in baseflow chemistry in response to changed atmospheric deposition and other environmental changes.
The following values have no corresponding Zotero field: publisher: Elsevier B.V. accession-num: 22200374
Keywords: Alkalinity; Base cations; nitrogen; Quercus ilex; Streamwater chemistry; Sulphate

Effects of environmental stress on forest crown condition in Europe. Part II: Estimation of stress induced by meteorology and air pollutants - Leeuwen, E. P. Van; Hendriks, KCMA (Water, Air, & Soil Pollution, 2000)
In order to assess the relationship between environmental stress and crown condition of forest trees monitored since 1986 in Europe, estimates of stress factors, including temperature stress, drought stress and air pollution stress, were derived with the best data, methods and models currently available. This paper presents information on the methods used to derive such stress factors, and on the overall ranges, the temporal trends, the spatial distribution and the reliability of the calculated stress factors. The temperature stress indices did not show much temporal variation between 1985 to 1995. As expected spatial patterns were north-south orientated, going from colder northern regions to warmer southern regions. The calculated relative transpiration showed a more complex pattern, coinciding to a large extend with patterns of rainfall and temperature. Potential acid deposition decreased between 1986 and 1992, but remained fairly constant after 1992. The strong decrease was mainly the result of the decrease in SOx deposition, and to a small decrease in NOy deposition. Highest levels of the S and N deposition were calculated in Central and Western Europe. Base cation deposition was largest in coastal areas and in southern Europe. This is mainly due to soil dust, Sahara dust and sea salt. Base cation deposition can compensate almost entirely for the potential inputs in the south of Europe, whereas in central Europe it equalled about 25% of the potential acid input. A comparison between site speciﬁc modelled deposition and deposition derived from throughfall data showed that the total acid deposition is usually overestimated by the model, whereas the total nitrogen deposition is underestimated, especially at plots with high nitrogen loads. There is, however, a signiﬁcant correlation between measured and modelled data for all S and N deposition, thus allowing their use in a statistical analyses.
Keywords: acidity; air pollution; ammonia; atmospheric deposition; Base cations; deposition model; Drought; nitrogen oxides; Ozone; sulphur; temperature stress; water balance